Signum distinctivum melodicum rękopisu Kraków, AiBKKK, Ms 45 .......... 219 - Białkowski, Mariusz (Graduał wawelski (Kraków, AiBKKK, Ms 45): Studium przypadku, 2025)
SIGNUM DISTINCTIVUM MELODICUM OF THE MANUSCRIPT KRAKÓW, AIBKKK, MS 45Each manuscript is created in a specific writing environment (time of writing and content) and has its specific purpose. These elements define its identity. The notation of the manuscript examined, Kraków, AiBKKK, Ms 45, is legible and records the 15th-century melodies with neumatic signs that have Metzen-German characteristics with Kraków elements. In light of the original Gregorian compositions (10th century), the examined notation has already been significantly simplified in terms of the neumes used and the melodies of the pieces. Such simplification is an expression of the liturgical and musical tendencies of the time, but maintains the characteristic features that constitute the identity of the Kraków school of manuscripts and the performance tradition.